2021
DOI: 10.3390/ijerph18168364
|View full text |Cite
|
Sign up to set email alerts
|

Differential Access to Park Space Based on Country of Origin within Miami’s Hispanic/Latino Population: A Novel Analysis of Park Equity

Abstract: Some U.S.-based park equity studies reveal that affluent and White neighborhoods have privileged access to greenspace. In such studies in the U.S. and elsewhere, park access indicators are typically examined in relation to measures of income, housing tenure, and broad race/ethnicity categories (e.g., Hispanic/Latino, Black, and White in the U.S.). The treatment of people as monolithic ethnic groups in park equity research is potentially misleading, particularly in global cities where ethnic populations are hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Existing evidence demonstrated that certain structural determinants of health such as residing in disadvantaged neighborhoods elevates the likelihood of poor health outcomes [8]. Hispanics tend to live in disadvantaged neighborhoods (e.g., lower socioeconomic status), which may lead to unhealthy behaviors and poor health outcomes [9][10][11][12]. For example, in a large metropolitan city, Hispanics are more likely to live in lower-income neighborhoods with greater density of fast-food restaurants [13].…”
Section: Introductionmentioning
confidence: 99%
“…Existing evidence demonstrated that certain structural determinants of health such as residing in disadvantaged neighborhoods elevates the likelihood of poor health outcomes [8]. Hispanics tend to live in disadvantaged neighborhoods (e.g., lower socioeconomic status), which may lead to unhealthy behaviors and poor health outcomes [9][10][11][12]. For example, in a large metropolitan city, Hispanics are more likely to live in lower-income neighborhoods with greater density of fast-food restaurants [13].…”
Section: Introductionmentioning
confidence: 99%